Impact of Work Life Balance on Stress Level and Performance - Rimisha Budhathoki; Dr. Deepa Pandey; Dr. Jyotsana Shukla (International Journal of Indian Psychȯlogy, 2025)
Work-life balance, or WLB, remains one of the most important modern concerns for employees as it relates to their overall satisfaction, health, and performance at work. This research aims to study the interplay between WLB, stress, and productivity through surveys and interviews with professionals from different fields. Our analysis emphasizes that neglecting personal life in favor of work is one of the strongest stressors affecting an individual’s health and performance. Organizations that adopt policies like flexible hours and soft benefits have higher employee productivity because these polices lead to increased employee satisfaction. Our findings illustrate the importance of organizational policies for creating a balanced work environment. In light of heightened global competition, companies need to formulate robust policies aimed at creating work-life balance within the organization to improve the health and productivity of their employees. Focusing on employee well-being helps both—organizations and employees—achieve stronger performance in the future.